Comparison between cone-beam computed tomography and direct digital intraoral imaging for the diagnosis of periapical pathology - Arpita Rai; Krishna Burde; Kruthika Guttal; Venkatesh G Naikmasur (Wolters Kluwer Medknow Publications, 2016)
Purpose: Early precise evaluation of periapical inflammatory lesions is necessary not only for diagnosis but also for treatment and follow-up. This study was performed to compare direct digital intraoral periapical images with three-dimensional (3D) images acquired from cone-beam computed tomography (CBCT) for the diagnosis and treatment planning of periapical pathology. Materials and Methods: Sixty teeth with clinical and/or radiographic evidence of periapical pathology were examined with direct digital imaging (DDI) and CBCT technique. Both the image dataset were evaluated by three oral radiologists. Numbers of roots and root canals, presence and location of periapical lesions, size of the lesion, root resorption and root fracture, and relation of the lesion to cortical bone and neighboring structures were studied. Cone-beam computed tomography periapical Index (CBCTPAI) was used and the values were compared using Wilcoxon-matched pairs test. The scores obtained for the 5-point scale for presence/absence of periapical lesion were also compared using Wilcoxon-matched pairs test. Results: Among 60 teeth, both the techniques demonstrated periapical lesions in 52 teeth, and an additional 5 teeth were found to have periapical lesions in the CBCT images. In regards to individual roots, 67 lesions were found in both the techniques, and 33 more roots were found to have lesions in CBCT images. Statistical analysis showed significant difference in both the imaging modalities for ascertaining the presence or absence of lesion on the 5-point scale and significant difference between DDI and CBCT in relation to the CBPAI scores. Conclusions: A high-resolution 3D technique can be of value for diagnosis of periapical problems, especially for multirooted teeth. CBCT is a promising technology for the diagnosis and management of periapical pathology.